IDENTIFIKASI KELUHAN MUSKULOSKELETAL DENGAN NORDIC BODY MAP DITINJAU DARI KESALAHAN POSISI DUDUK DAN INDEKS KESEGARAN JASMANI PADA PERAJIN PERAK DI DESA PULO KECAMATAN TEMPEH KABUPATEN LUMAJANG - Anita Dewi Prahastuti S.; Rika Siskandini (Jurnal Ilmu Kesehatan Masyarakat, 2009)
Musculoskeletal disorders (MSDs) is a sigh of ill, painful, stiff and others in muscles system (musculoskeletal) such as tendon, blood vessel, hinge, bone which are caused by work activities. Pulo Village located in Tempeh District Lumajang Regency is the silver industry center which has musculoskeletal disorder risk in every production process. The causal factor is individual characteristics, for instance period of work and non-ergonomic of work attitude such as sitting position. This research aimed to analyze correlation between individual characteristics as well as sitting position and musculoskeletal disorder towards the silver artisan in Pulo Village Tempeh District Lumajang Regency. It was an observational analytic research by cross sectional approach. The population in this research was 155 persons. The samples which were 60 persons were determined by the formula developed by Snedecor and Cochran and simple random sampling technique. Collecting of data used interview, questioner and observation guidance. Meanwhile, analysis of data used Spearman and Statistic of Lambda Test with α = 0,05. The results of analysis indicate that there is a relation of exercise habit (p=0.005), , physical fitness (p=0.0001) and sitting position (p=0.028) to the musculoskeletal disorder. Based on this research, it is expected of doing socialization of musculoskeletal disorder prevention to the silver artisans through practicing of muscle stretching, moving to the more ergonomic in sitting position, doing sport continuously, and having more drinking water. Keywords: sitting  position, musculoskeletal disorders, Nordic Body Map,occupational safety and health